Energy Utilization Technology of Agriculture and Forestry Waste - . Hardoyo (Bandar Lampung University (UBL), 2013)
The increasing of fossil energy consumption and will be limited of fossil energy source, cause important to develope alternative energy. One of alternative energy is energy from biomass waste, like agriculture and forestry waste. Those biomass wastes contain cellulose, hemicellulose and lignin. The utilization technology of biomass waste could be done by thermochemical and biochemical process. Direct combustion, gasification, convertion to solid fuel and esterification are the termochemical process, that produce heat supply generator , flameable gas, solid fuel and diesel fuel. Anaerobic digestion and ethanol fermentation are the biochemical convertion, that produce methane gas and ethanol. The energy bioconverrtion technology to convert ethanol from biomass waste are pretreatment, hydrolysis, fermentation, distillation and dehydration.